Influence of the Curvature Radius on Contact Characteristic of Deep Groove Ball Bearing - Zhong Conghua (Jixie chuandong)
The contact characteristics of deep groove ball bearing（ DGBB） is one of the important factors that influence the DGBB property,for analyzing the influence of curvature radius on the contact characteristics of DGBB,taking the SKF618 /8 single row DGBB used in the planetary transmission mechanism as example.The stress,strain,velocity,contact force are simulated and analyzed based on the finite element software,and the influence of different curvature radius of inner ring,outer ring and the diameter of the roller on its contact characteristics are analyzed. The results show that the velocity,stress and strain of roller are variations in the form of peaks and troughs,and the stress,strain are mainly concentrated in the contact area between the roller and the inner or outer circle. The roller stress is increased with the curvature radius of inner ring,outer ring and rolling element diameter,moreover,the speed of the rolling element is greater with the longer of the distance to the center of rotation. Furthermore,the volatility and contact force of DGBB between the rolling element and inner or outer ring have the similar size,which basically the same with the radial load value,but the force between rolling element and maintains is small.